Recent statistical studies of zinc and its effect on the human body (Texas Journal of Multidisciplinary Studies, 2022)
Compared with many other metal ions with similar chemical properties, zinc is relatively harmless. Except when exposed to high doses, it has toxic effects, making it severe Intoxication; Long-term high doses of zinc also interfere with copper absorption. Hence it causes copper deficiency. Since zinc has a prominent role in brain cell death, cytotoxicity as a result of this includes ischemia or shock accumulation of free zinc. Rather than being a toxic metal (ion), zinc is an essential element. While overexposure poisoning is rare, zinc deficiency is widespread and has a detrimental effect on neuronal growth and immunity, and in severe cases its consequences are fatal. Deficiency caused by poor diet and foods with low bioavailability, aging, disease, or unregulated homeostasis is a more common hazard to human health. This study includes a statistical explanation of the natural ratios found in the human body, as well as statistical studies on the protocol used to take zinc in the quantities that must be taken to avoid infection with viruses, especially the Corona virus.